Developing an Instrument to Assess Writing Skills in Arabic as a Second Language: A Confirmatory Factor Analysis Approach - Lalu Agus Pujiartha; Apri Wardana Ritonga; Ayu Desrani; Agus Supriatna (Institut Agama Islam Negeri Imam Bonjol Padang, 2025)
This study aims to develop an assessment instrument for Arabic writing skills as a second language using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). The instrument was developed based on the Oriondo and Antonio model, with a sample of 248 students who completed a writing test. Data were analyzed using R-Studio software for EFA, CFA, and descriptive statistics. The EFA results revealed one main factor, with eigenvalues and factor loadings above 0.6, indicating a consistent factor structure. In CFA, the four dimensions of writing skills Ideas and Content, Structure and Organization, Style and Rhetoric, and Language and Grammar demonstrated strong factor loadings and good model fit, confirming the robustness of the instrument. The instrument also showed high internal consistency and strong construct validity. This instrument can be practically used by educators and language program administrators to evaluate and enhance students’ writing proficiency in Arabic as a second language. This study produces a valid and reliable instrument for assessing Arabic writing skills as a second language in higher education.